Immunotherapy for Drug Abuse - Shen, Xiaoyun; R. Kosten, Thomas (CNS & Neurological Disorders - Drug Targets, 2011)
Substance use disorders continue to be major medical and social problems worldwide. Current medications for substance use disorders have many limitations such as cost, availability, medication compliance, dependence, diversion of some to illicit use and relapse to addiction after discontinuing their use. Immunotherapies using either passive monoclonal antibodies or active vaccines have distinctly different mechanisms and therapeutic utility from small molecule approaches to treatment. They have great potential to help the patient achieve and sustain abstinence and have fewer of the above limitations. This review covers the cocaine vaccine development in detail and provides an overview of directions for developing anti-addiction vaccines against the abuse of other substances. The notable success of the first placebo-controlled clinical trial of a cocaine vaccine, TA-CD, has led to an ongoing multi-site, Phase IIb clinical trial in 300 subjects. The results from these trials are encouarging further development of the cocaine vacine as one of the first anti-addiction vaccines to go forward to the U.S. Food and Drug Administration for review and approval for human use.
Keywords: Cocaine